Investigating Clinical Benefits of a Novel Sleep-Focused Mind-Body Program on Gulf War Illness Symptoms: A Randomized Controlled Trial. Issue 6 (July 2017) - Nakamura, Yoshio; Lipschitz, David L.; Donaldson, Gary W.; Kida, Yuri; Williams, Samuel L.; Landward, Richard; Glover, Don W.; West, Gavin; Tuteja, Ashok K.
ABSTRACT: Objective: Mind-Body Bridging (MBB) has been shown to be effective for improving disturbed sleep. In this prospective randomized controlled trial, we evaluated the efficacy of sleep-focused MBB compared with sleep education control (SED) for improving sleep in previously deployed Gulf War veterans. Methods: US military service members with sleep and physical health complaints who were deployed in 1990–1991 were randomized to receive three weekly sessions of either MBB ( n = 33) or SED ( n = 27) between 2012 and 2015. The primary outcome of Medical Outcomes Study Sleep Scale was completed at baseline, weekly during treatment, postintervention, and 3-month follow-up. Secondary outcome measures for posttraumatic stress disorder, depression, fatigue, quality of life, symptom severity, and mindfulness were completed at baseline, postintervention and 3-month follow-up. Salivary samples were collected at five time points per day at each visit for cortisol and α-amylase assessment. Clinician-administered assessments of sleep and co-occurring conditions were conducted at baseline and postintervention. Results: MBB was significantly more efficacious than SED in reducing disturbed sleep at follow-up ( F (1, 180.54) = 4.04, p = .046). In addition, self-reported posttraumatic stress disorder ( F (1, 56.42) = 4.50, p = .038) for the treatment effect, depression ( F (1, 93.70) = 4.44, p = .038), and fatigue symptoms ( F (1, 68.58) = 3.90, p = .050) at follow-up improved in MBB compared with those in SED. Consistently higher percentages of veterans in MBB reported improvements of sleep, pain, and composite sleep/general co-occurring symptoms at the postclinical evaluation, as compared with veterans in SED. Finally, the mean waking level of salivary α-amylase in the MBB declined to a greater extent than that in the SED, at follow-up ( F (1, 88.99) = 3.78, p = .055), whereas no effects were found on cortisol. Conclusions: Sleep-focused MBB can improve sleep and possibly also co-occurring symptoms in Gulf War veterans. Clinical Trial Registration: Clinicaltrials.gov, NCT01543997. Abstract : Supplemental digital content is available in the text.